TRADISI NYANDAK MASYARAKAT SASAK DALAM PERSPEKTIF FIQH MUâAMALAH - Musawar, Musawar (JURNAL PENELITIAN KEISLAMAN, 2011)
This article discusses sandak, a common tradition of muamalah (Islamic transaction) among the Sasak in Lombok. The tradition constitutes a model of transaction that contains commercial and economic value where the creditor takes over the debtorâs land or rice field as a secure deposit. There is no exact equivalent term for sandak in Islamic law, and yet it can still be classified as sale, lease and crop sharing which is clearly part of muaâmalah. However, seen from the concept of al-rahn (mortgage), al-qarld (loan/lease) and al-riba (interest), sandak is legally problematic because some aspects of it are forbidden. To avoid being trapped in an illegal transaction, the Sasak, who mostly follow the Shafiâite School, tend to be flexible by adopting the Hanafite school which is believed to be more accommodative to this tradition than the first school. There are two models of sandak. First, the creditor takes benefits of the secure deposit such as the rice field or garden upon the debtorâs approval, a practice permitted by the Hanafite. Second, the parties involving in this transaction use the principle of baây al-wafaâ, that is transaction to fulfill humanâs need, arguing that the need may elevate emergency.